Motivation, Self Disclosure dan Psychological Well Being pada Perempuan Dewasa Muda Ibu Kota Melalui Media Sosial Instagram - Derira Harahap; Hendriyani Hendriyani (Mahesa Research Center, 2023)
This research analyzes the influence of Motivation, Self disclosure, and Psychological Well- Being on young adult women in the capital city through the social media platform Instagram. The purpose of this research is to find out the motivation of Instagram users to do self disclosure. Furthermore, this research was also conducted to see the effect of self disclosure on psychological well-being. This study adopts a descriptive quantitative research design with an explanatory approach, utilizing a questionnaire administered to 200 young adult female respondents in the capital city. Using PLS SEM as a data processing tool. This research delves deeper into the topic of self disclosure specifically focusing on young adult women residing in the capital city. The study provides a more specific understanding of the relationship between motivation for self disclosure and its impact on psychological well-being. The findings of this research indicate that individuals with high levels of motivation for self disclosure and high levels of openness tend to have positive levels of psychological well-being. In other words, individuals who have a strong motivation to share about themselves and actively express themselves to a high degree tend to experience positive psychological well-being.